Impact Evaluation of VKN–NIMHANS–ECHO Model of Capacity Building for Mental Health and Addiction: Methodology of Two Randomized Controlled Trials. Issue 6 (December 2020) - Kumar, Channaveerachari Naveen; Chand, Prabhat Kumar; Manjunatha, Narayana; Math, Suresh Bada; Shashidhara, Harihara Nagabhushana; Basavaraju, Vinay; Thirthalli, Jagadisha; Manjappa, Adarsha Alur; Parthasarathy, Rajani; Murthy, Pratima; Ibrahim, Ferose Azeez; Jagtap, Namrata; et al.
Background: Bridging the alarming treatment gap for mental disorders in India requires a monumental effort from all stakeholders. Harnessing digital technology is one of the potential ways to leapfrog many known barriers for capacity building. Aim and Context: The ongoing Virtual Knowledge Network (VKN)–National Institute of Mental Health and Neurosciences (NIMHANS)–Extension of Community Health Outcomes (ECHO) (VKN–NIMHANS–ECHO: hub and spokes model) model for skilled capacity building is a collaborative effort between NIMHANS and the University of New Mexico Health Sciences Centre, USA. This article aims to summarize the methodology of two randomized controlled trials funded by the Indian Council of Medical Research (ICMR) designed to evaluate the effectiveness of the VKN–NIMHANS–ECHO model of training as compared to training as usual (TAU). Methods: Both RCTs were conducted in Karnataka, a southern Indian state in which the DMHP operates in all districts. We compared the impact of the following two models of capacity building for the DMHP workforce (a) the VKN–NIMHANS–ECHO model and (b) the traditional method. We use the SPIRIT (Standard Protocol Items: Recommendations for Interventional Trials) statement to describe the methods of these two trials. Trial 1 is to evaluate the "Effectiveness of addition of Virtual-NIMHANS–ECHO tele-mentoring model for skilled capacity building in providing quality care in alcohol use disorders by the existing staff of DMHP districts of Karnataka." Hub for trial 1 was set up at NIMHANS and the spokes were psychiatrists and other mental health professionals headquartered in the district level office. Trial 2 assesses the implementation and evaluation of the NIMHANS–ECHO blended training program for the DMHP workforce in a rural south-Indian district of Karnataka state. The hub for trial 2 was set up in the district headquarter of Ramanagaram. Hub specialists are DMHP psychiatrists, whereas spokes are the non-doctor workforce (including auxiliary nurse midwives [ANMs] and accredited social health activists [ASHA] workers) medical officers of primary health centers. The location of the HubHub differs in these two studies. Both trials are funded by the ICMR, Government of India Discussion: Both these trials, though conceptually similar, have some operational differences which have been highlighted. If demonstrated to be effective, this model of telementoring can be generalized and widely merged into the Indian health care system, thus aiding in reducing the treatment gap for patients unable to access care.